Advancements in climate-resilient propagation of ornamental plants: Strategies for a changing environment - Shabnam, P; Puja, S; Shilpa, K; Yogendra, A; Vivek, B (Plant Science Today, 2025)
The increasing impact of climate change has necessitated the development of climate- resilient ornamental plants, which can withstand extreme environmental conditions while maintaining aesthetic value. This paper explores recent advancements in the propagation of these plants, focusing on strategies that enhance their resilience to shifting climate patterns. Key areas of innovation include genetic approaches, such as drought and heat tolerance breeding, as well as the use of CRISPR technology to create stress-resistant plant varieties. The role of modern propagation techniques, including tissue culture, micropropagation and sustainable water-efficient methods, is examined in the context of climate adaptation. Additionally, advances in technology, such as AI, IoT and automated systems, are transforming plant propagation by improving environmental monitoring and optimizing growing conditions. Case studies on the successful cultivation of climate-resilient ornamental plants demonstrate their potential in urban landscaping, where climate-adapted species can contribute to sustainable, low-maintenance green spaces. The paper also highlights the importance of integrating eco-friendly practices, such as regenerative horticulture and water smart landscaping, in creating resilient urban environments.